Lung Injuries Induced by Inden0(1,2,3-Cd)Pyrene In Rats On Garlic Supplementation - Movassagh, Sanaz (2007)
The impact of air pollution on health and economic well-being of nation is an important worldwide issue. Indeno[l,2,3-cdlpyrene (IP) is a particulate matter amongst environmental pollutants found in the Malaysian haze episodes and was claimed to induce deleterious effects on humans or animals. However, such claims have never been scientifically substantiated. In manifesting the noxious effects of haze and in view of developing strategies and bringing about a remission of such effects in humans, the symptoms of both acute exposure and chronic response to IP were studied on the pulmonary system of rats. The acute exposure studies were conducted to evaluate the histopathological and ultrastructural changes and detection of apoptotic cells in the lung of rats following treatment with IP with or without garlic supplementation. Furthermore, the immunological responses and elastolytic enzymes activities were also determined. The IP-treated rats received 13 ng (6.5 ~ 1 o)f IP that was instilled intra-tracheally without garlic supplementation. Rats from the garlic (G) group were fed the basal ration containing garlic incorporated at the rate of 80 mglkg body-weight/rat/day while those from the G+IP group fed on garlic diet for two weeks before instillation with IP. All animals were sacrificed at 8, 16, 24 and 32 hours (hrs) post-instillation (pi.) and according to the respective interval design. Histopathological alterations were studied on haematoxylin-eosin (H&E) stained sections and ultrastructural changes revealed by transmission electron microscope (TEM). Apoptosis assessment was made on terminal desxynucleotidyl transferase-mediated dUTP nick-end labeling (TUNEL) analysis and caspase 3 colorimetric assay. The broncho-alveolar lavage (BAL) assays, ELISA method and alveolar macrophages (AM0) activities assay were used to detect the elastolytic enzymes activities and lung defense. Histopathological, ultrastructural, TUNEL and caspase 3 assays findings showed apoptosis which advances with time in the pneumocytes and bronchial epithelium of all IP-treated rats euthanised at the respective time. In addition, inflammation, necrosis and epithelisation were also observed in the IP group. Likewise, the IP group had the highest elastase-like and neutrophil elastase specific activities but the lowest IgA and IgG levels, AM0 phagocytosis, and intracellular killing activities of AM0 in the BAL. Supplementation with garlic was able to minimize the deleterious effect of IP. In the chronic response studies, in addition to the other parameters measured in the acute study, an assessment on the level of glutathione S-transferase (GST) was also made. Similarly, there was an additional treatment group that was instilled with IP once at the beginning of the study and fed with garlic during the whole period of experiment (IP+G) to assess the effect of consumption of garlic during the response to IP.The microscopic and ultrastructure studies revealed evidence of apoptosis, inflammation, necrosis and epithelisation in the lung of rats treated with IP. In addition, rats treated with IP had the lowest levels of IgA, IgG, alveolar macrophages activities and GST specific activity in the lung. Furthermore, there was a dreadful effect on elastolytic enzymes activities present in the IP-treated rats. In contrast, the IP-treated groups fed with garlic showed significant improvement towards normal histology of the lung or trachea. However, it was found that regularly consumption of garlic during the response to IP have a better result than a prophylactic regime before response. In conclusion, IP poses as an environmental hazard to the lungs of rats triggering deleterious changes either due to short exposure or long term response and garlic has a great potential in alleviating these adverse effects.